Reducing the New Inmates' Anxiety through Rational Emotive Behavior Therapy with Patronage Counseling Technique - Farid Junaedi; Fattah Hanurawan; Arbin Janu Setiowati; Muhammad Ramli (Ital Publication, 2022)
Recurring cases of suicide, escapement, riots, and overcapacity have been observed in correctional institutions in Indonesia. Mental health issues are one of the causes of such a phenomenon. The emergence of this mental health issue may negatively impact inmates and cause disturbances in correctional institutions. Rational Emotive Behavior Therapy (REBT) focuses on transforming an irrational concept into a rational belief. This study aims to investigate the effects of REBT counseling with patronage technique on reducing anxiety levels. This new Patron-Client platform, equipped with the signification of gratitude and contentment, becomes a new form of proper counseling in a correctional institution. This study adopted the quasi-experiment before-after method with the Solomon four-group design. To garner the data, it involved four groups divided into two experimental and two control groups, consisting of 240 research population and 160 research subjects. ANOVA and T-test analysis were used to further analyze the obtained data. The findings show significantly different anxiety levels in the inmate groups before and after the treatment. Besides, no difference was observed in the inmates who did not receive the treatment. This study concludes that REBT counseling with patronage technique significantly decreases the inmates’ anxiety levels in the correctional institution. Doi: 10.28991/ESJ-2022-06-02-08 Full Text: PDF